Computer union catalogues in Lithuania - Striogienė, Aurelija (Information & Media, 1996)
The lack of union catalogues in Lithuania is a problem today. The article describes traditional forms of union catalogues at first. There are some tables which analyze the printed union catalogues of the 1959–1995 period.The creation of computer union catalogues in Lithuania is problematic today. We can find information about new foreign periodical publications in the computer union catalogue. The beginning of its creation was in 1990. A computer union catalogue of foreign books received in Lithuanian libraries will be created in 1996.
Keywords: -